THE USE OF SURVEY QUESTION READ RECITE REVIEW (SQ3R) STRATEGY TO ENHANCE THE LEARNERS MOTIVATION IN COMPREHENDING ANNOUNCEMENT TEXTS (THE CASE OF SEVENTH GRADE STUDENTS OF SMPN 3 CIAWIGEBANG KUNINGAN) - Triwardani, Henni Rosa (Syntax Literate, 2017)
The aim of this study- to describe the implementation of SQ3R strategy in teaching reading of announcement texts, to describe the enhancement of students` motivation in reading announcement texts through the use SQ3R strategy, and to describe the students` enhancement of reading comprehension on announcement texts- was based on some weaknesses of students` vocabulary mastery and students` low score of reading comprehension that were found in classroom. The Subject was twenty eight of seventh grade students of SMPN 3 Ciawigebang Kuningan . By using Action Research approach, the research applied Planning, Action, Observation, and Reflection phases. It was conducted in two cycles in which each cycle consisted of three meetings. The data collection were administered through observation, questionnaire, interview, and reading comprehension pre-test and post-test. The results of study showed the implementation of SQ3R was good, students` motivation in following reading class was high, and students` reading comprehension score increased. The suggestion for future research is to conduct comparative research on SQ3R strategy to enhance students` reading comprehension between students with upper and lower ability. Key Words: SQ3R Strategy, Reading, Announcement Text, Motivation